The structure of CYP101D2 unveils a potential path for substrate entry into the active site. - Yang, W; Bell, S; Wang, H; Zhou, W; Bartlam, M; Wong, L; Rao, Z (2011)
The cytochrome P450 CYP101D2 from Novosphingobium aromaticivorans DSM12444 is closely related to CYP101D1 from the same bacterium and to P450cam (CYP101A1) from Pseudomonas putida. All three are capable of oxidizing camphor stereoselectively to 5-exo-hydroxycamphor. The crystal structure of CYP101D2 revealed that the likely ferredoxin-binding site on the proximal face is largely positively charged, similar to that of CYP101D1. However, both the native and camphor-soaked forms of CYP101D2 had open conformations with an access channel. In the active site of the camphor-soaked form, the camphor carbonyl interacted with the haem-iron-bound water. Two other potential camphor-binding sites were also identified from electron densities in the camphor-soaked structure: one located in the access channel, flanked by the B/C and F/G loops and the I helix, and the other in a cavity on the surface of the enzyme near the F helix side of the F/G loop. The observed open structures may be conformers of the CYP101D2 enzyme that enable the substrate to enter the buried active site via a conformational selection mechanism. The second and third binding sites may be intermediate locations of substrate entry and translocation into the active site, and provide insight into a multi-step substrate-binding mechanism.